2016
DOI: 10.1016/j.ribaf.2016.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Euphoria in financial markets: How Indian companies generate value in their cross-border acquisitions

Abstract: In this paper, we investigate the effect of euphoria on returns derived by Indian companies in their cross-border acquisitions. Cognitive legitimacy generated at the country level facilitated firms in deriving higher value from internationalization. In addition, overoptimism after the legitimacy-building event led to euphoria in financial markets and short-term abnormal returns. Hence we argue that the springboard effect created by legitimacy is short-lived, as euphoria fades away over time. Using cross-border… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 90 publications
1
0
0
Order By: Relevance
“…The reason for positive but diluted performance appears to be the attractive valuation of the targets available overseas due to global crisis and at the same time, the recession in these economies on whom the long-term performance is dependent. The findings of this study are consistent with Acharya, Shin and Yorulmazer (2011), Beltratti and Paladino (2013), Gubbi and Elango (2016), Nicholson and Ayten (2016), Reddy et al (2014) and Yoon and Lee (2016) who reported the gains from assets at fire-sale prices during the crisis period. The evidence presented in the study corroborates previous empirical evidence of positive abnormal returns to the announcement of CBA (Bhagat, Malhotra, & Zhu, 2011; Boateng et al, 2008; Nicholson & Salaber, 2013; Wang & Boateng, 2007; Zhou et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…The reason for positive but diluted performance appears to be the attractive valuation of the targets available overseas due to global crisis and at the same time, the recession in these economies on whom the long-term performance is dependent. The findings of this study are consistent with Acharya, Shin and Yorulmazer (2011), Beltratti and Paladino (2013), Gubbi and Elango (2016), Nicholson and Ayten (2016), Reddy et al (2014) and Yoon and Lee (2016) who reported the gains from assets at fire-sale prices during the crisis period. The evidence presented in the study corroborates previous empirical evidence of positive abnormal returns to the announcement of CBA (Bhagat, Malhotra, & Zhu, 2011; Boateng et al, 2008; Nicholson & Salaber, 2013; Wang & Boateng, 2007; Zhou et al, 2015).…”
Section: Discussionsupporting
confidence: 90%